Safety of penicillamine and trientine in the treatment of Wilson’s disease: An analysis of the FDA Adverse Event Reporting System (FAERS) database - Wenlong Qian; Kou Xu; Shuo Li; Zhuo Zhang; Xiaoxiao Hou; Bingjie Min; Jia Ling; Xinyu Zhu; Hui Zhou; Wenjuan Xu; Wenming Yang; Shijian Cao; et al. (PLoS ONE, 2025)
Background Penicillamine(D-Penicillamine) and trientine are first-line therapies for Wilson’s Disease (WD), yet real-world data on their adverse events (AEs) remain scarce. We analyzed the FDA Adverse Event Reporting System (FAERS) to comprehensively assess the safety of penicillamine and trientine in WD treatment. Methods AEs for penicillamine and trientine (2004Q1–2024Q4) were analyzed using Proportional Reporting Ratio (PRR), Reporting Odds Ratio (ROR), and Bayesian Confidence Propagation Neural Network (BCPNN). Results We found 1,452 and 760 AEs related to penicillamine and trientine, respectively. In all adverse event (AE) reports, the ratio of females to males was approximately 1.3, with the highest proportion of AE reports in the 21–30 age group, and the largest number of AE reports coming from the United States. Signal detection showed that the most commonly reported AEs for penicillamine and trientine were drug hypersensitivity and tremor, respectively, with the highest proportions in the SOC categories of immune system disorders and gastrointestinal disorders. The main AEs for both drugs involved condition aggravated, and identified potential safety signals requiring further validation for the two drugs, such as decreased bone density and brain atrophy for penicillamine, and memory impairment, oesophageal ulcer and starvation for trientine. In addition, we found that women were more likely to experience drug hypersensitivity in penicillamine adverse event reports, while men were more likely to experience cutis laxa. Conclusion This study reveals the characteristics of AEs and potential associated risks in the clinical application of penicillamine and trientine, emphasizing individualized medication and vigilant monitoring strategies to provide guidance for safe medication use.